Hydrophobic and metallophobic surfaces: Highly stable non-wetting inorganic surfaces based on lanthanum phosphate nanorods - Sankar, S.; Nair, Balagopal; Suzuki, T.; Anilkumar, G.; Padmanabhan, M.; Hareesh, U.; Warrier, K. (Nature Publishing Group, 2016)
Metal oxides, in general, are known to exhibit significant wettability towards water molecules because of the high feasibility of synergetic hydrogen-bonding interactions possible at the solid-water interface. Here we show that the nano sized phosphates of rare earth materials (Rare Earth Phosphates, REPs), LaPO 4 in particular, exhibit without any chemical modification, unique combination of intrinsic properties including remarkable hydrophobicity that could be retained even after exposure to extreme temperatures and harsh hydrothermal conditions. Transparent nanocoatings of LaPO 4 as well as mixture of other REPs on glass surfaces are shown to display notable hydrophobicity with water contact angle (WCA) value of 120° while sintered and polished monoliths manifested WCA greater than 105°. Significantly, these materials in the form of coatings and monoliths also exhibit complete non-wettability and inertness towards molten metals like Ag, Zn, and Al well above their melting points. These properties, coupled with their excellent chemical and thermal stability, ease of processing, machinability and their versatile photo-physical and emission properties, render LaPO 4 and other REP ceramics utility in diverse applications.